Collaborative Teaching Program: sharing industrial practice and expertise / Kuan Woei Keong - Kuan, Woei Keong (Unit Penerbitan PKAPP, 2024)
On 23 October 2023, Mr. Muhammad Haniff bin Ahmad, a research officer from the Engineering Research Center at the Malaysian Agricultural Research and Development Institute (MARDI) was invited as a speaker for a collaborative teaching program. This program is aimed at enhancing the knowledge of students in the industrial sector. The topic of presentation was “Water Recycling System in Sustainable Water Management Approach for Paddy Production.” The primary objective of the talk was to shed light on the critical role of water recycling systems in promoting sustainable water management practices within the context of paddy cultivation.